Akt/PKB activation and insulin signaling: a novel insulin signaling pathway in the treatment of type 2 diabetes - Mackenzie RWA (Dove Medical Press, 2014)
Richard WA Mackenzie, Bradley T Elliott Department of Human and Health Sciences, Facility of Science and Technology, University of Westminster, London, UK Abstract: Type 2 diabetes is a metabolic disease categorized primarily by reduced insulin sensitivity, β-cell dysfunction, and elevated hepatic glucose production. Treatments reducing hyperglycemia and the secondary complications that result from these dysfunctions are being sought after. Two distinct pathways encourage glucose transport activity in skeletal muscle, ie, the contraction-stimulated pathway reliant on Ca2+/5′-monophosphate-activated protein kinase (AMPK)-dependent mechanisms and an insulin-dependent pathway activated via upregulation of serine/threonine protein kinase Akt/PKB. Metformin is an established treatment for type 2 diabetes due to its ability to increase peripheral glucose uptake while reducing hepatic glucose production in an AMPK-dependent manner. Peripheral insulin action is reduced in type 2 diabetics whereas AMPK signaling remains largely intact. This paper firstly reviews AMPK and its role in glucose uptake and then focuses on a novel mechanism known to operate via an insulin-dependent pathway. Inositol hexakisphosphate (IP6) kinase 1 (IP6K1) produces a pyrophosphate group at the position of IP6 to generate a further inositol pyrophosphate, ie, diphosphoinositol pentakisphosphate (IP7). IP7 binds with Akt/PKB at its pleckstrin homology domain, preventing interaction with phosphatidylinositol 3,4,5-trisphosphate, and therefore reducing Akt/PKB membrane translocation and insulin-stimulated glucose uptake. Novel evidence suggesting a reduction in IP7 production via IP6K1 inhibition represents an exciting therapeutic avenue in the treatment of insulin resistance. Metformin-induced activation of AMPK is a key current intervention in the management of type 2 diabetes. However, this treatment does not seem to improve peripheral insulin resistance. In light of this evidence, we suggest that inhibition of IP6K1 may increase insulin sensitivity and provide a novel research direction in the treatment of insulin resistance. Keywords: type 2 diabetes, insulin resistance, Akt/PKB, 5′-monophosphate-activated protein kinase